Pupae of the Nearctic species of Culicoides Latreille subgenus Monoculicoides Khalaf (Diptera: Ceratopogonidae) - Shults, Phillip; Borkent, Art (Zootaxa, 2018)
There are 160 valid species of Culicoides Latreille described from the Nearctic Region, but many are unknown as immatures or, although partially described, cannot be readily identified. We provide pupal diagnoses, descriptions, and a key to all seven known species of Culicoides subgenus Monoculicoides Khalaf occurring in the Nearctic biogeographic region. A diagnosis of several characters unique to this subgenus is provided to allow for the recognition of the included species from those of other subgeneric groupings. Microphotography of important morphological characters for both the key and descriptions are provided. This study highlights the usefulness of examining the pupae of Culicoides as a tool for species identification. The pupae of Culicoides grandensis Grogan & Phillips, C. occidentalis Wirth & Jones, and C. shemanchuki Grogan & Lysyk are newly described and those of C. riethi Kieffer, C. stigma (Meigen), and C. variipennis Wirth & Jones are redescribed in detail. The seventh species, C. sonorensis, was fully described recently.